Strategic Thinking in Identifying and Evaluating New Business Ideas of Master of Management Students at Andalas University - Al Hakim, Husnul Fikri; Games, Donard; Alfitman, Alfitman; Komalasari, Sanda Patrisia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to explore how strategic thinking plays a role in the process of identifying and evaluating new business ideas among Magister Management students at Universitas Andalas. In this context, strategic thinking is used to identify opportunities and challenges in business idea development, as well as to evaluate the feasibility and potential of business ideas through systematic methods. This research also examines the application of the How Might We (HMW) method in formulating business ideas and the Venture Idea Assessment (VIA) framework in evaluating the feasibility of business ideas. Data were collected through Focus Group Discussions (FGD) involving students and several professionals from the fields of entrepreneurship, academia, and investment. The results of the analysis using NVivo show that strategic thinking, which involves systematic problem-solving, market opportunity understanding, and risk analysis, plays a crucial role in the success of business idea identification and evaluation. The HMW method proved effective in helping students identify relevant problems, while the VIA framework provided a tool to assess business ideas based on market potential, operational feasibility, and existing risks. Overall, this research highlights the importance of strategic thinking in creating business ideas that are not only creative but also executable and market-accepted, as well as how the HMW method and the VIA framework can complement each other to form a more effective approach in developing sustainable new business ideas.